Una política exterior para grandes y pequeños países en Europa - Törnudd, Klaus (Revista Mexicana de Política Exterior, 2022)
The author explores the different challenges involved in the effort to coordinate a common foreign policy for all the members of the European Union (EU), who have to begin to overcome the traditional view of interest defined in strictly domestic terms. He admits that there has been important progress, which manifests in the already developed structures that make it possible to handle an integrated economy and collective defense mechanisms, although he does not fail to mention the risks implicit in a policy of integration that assumes the loss of identity by the less strong or the exclusion of basic players for the future of Europe: most particularly, Russia. The growing multitude of new and renewed challenges demands a flexible but imaginative attitude on the part of those responsible for designing a foreign policy that will have to be capable of recognizing diversity without weakening the Union.